Pandemic-era Participation in Public Lands Governance: Lessons From the USDA Forest Service - Floress, Kristin; Cohen, Alice (Frontiers in Sustainable Cities, 2022)
Public participation processes influencing National Forest management in the United States have shifted significantly because of the global COVID-19 pandemic. Although the United States Forest Service has used virtual participation tools in the past to support participation, the pandemic was the first time staff had to solely rely on such methods. Using the Trinity of Voice theory concepts of access, standing, and influence, we discuss how each has been and can be impacted by virtual vs. in-person public participation in federal land governance. Lessons are drawn from two peer-to-peer learning sessions among Forest Service staff in Fall 2020 and a case from the National Forests in North Carolina. Virtual participation can broaden access to processes that would primarily have taken place in-person as people were not limited by travel time or distance. Virtual methods may allow for greater use of adaptive technologies and therefore may increase participation access. Web meeting alternatives (e.g., telephone calls) can be used to increase participation access for those without reliable or affordable internet. However, planners trained in facilitating in-person meetings may not have the technical competencies necessary to ensure participants are able to effectively participate during virtual meetings, and misunderstandings that might be easily addressed in face-to-face settings can be more difficult to solve and ground rules for participation ignored more easily during virtual participation. We expect these lessons will support the work of other practitioners interested in supporting access, standing, and influence when designing virtual participation processes.